Mutual epithelium‐macrophage dependency in liver carcinogenesis mediated by ST18. Issue 5 (30th December 2016) - Ravà, Micol; D'Andrea, Aleco; Doni, Mirko; Kress, Theresia R.; Ostuni, Renato; Bianchi, Valerio; Morelli, Marco J.; Collino, Agnese; Ghisletti, Serena; Nicoli, Paola; Recordati, Camilla; Iascone, Maria; et al.
Abstract : The ST18 gene has been proposed to act either as a tumor suppressor or as an oncogene in different human cancers, but direct evidence for its role in tumorigenesis has been lacking thus far. Here, we demonstrate that ST18 is critical for tumor progression and maintenance in a mouse model of liver cancer, based on oncogenic transformation and adoptive transfer of primary precursor cells (hepatoblasts). ST18 messenger RNA (mRNA) and protein were detectable neither in normal liver nor in cultured hepatoblasts, but were readily expressed after subcutaneous engraftment and tumor growth. ST18 expression in liver cells was induced by inflammatory cues, including acute or chronic inflammation in vivo, as well as coculture with macrophages in vitro . Knocking down the ST18 mRNA in transplanted hepatoblasts delayed tumor progression. Induction of ST18 knockdown in pre‐established tumors caused rapid tumor involution associated with pervasive morphological changes, proliferative arrest, and apoptosis in tumor cells, as well as depletion of tumor‐associated macrophages, vascular ectasia, and hemorrhage. Reciprocally, systemic depletion of macrophages in recipient animals had very similar phenotypic consequences, impairing either tumor development or maintenance, and suppressing ST18 expression in hepatoblasts. Finally, RNA sequencing of ST18 ‐depleted tumors before involution revealed down‐regulation of inflammatory response genes, pointing to the suppression of nuclear factor kappa B–dependent transcription. Conclusion : ST18 expression in epithelial cells is induced by tumor‐associated macrophages, contributing to the reciprocal feed‐forward loop between both cell types in liver tumorigenesis. Our findings warrant the exploration of means to interfere with ST18‐dependent epithelium–macrophage interactions in a therapeutic setting. (Hepatology 2017;65:1708‐1719).